Airline e-ticket online purchase intention among university student / Mazlina Mahdzar ...[et al.] - Mahdzar, Mazlina; Sham, Aida Kamilia Khairom Azlin; Akib, Fauzan Azim; Mohmad Isa, Iffah Dayana; Hassan Basri, Nur Syarfa' (Universiti Teknologi MARA, 2021)
Purchasing products and services via online is an important way of doing business for many tourism and hospitality intermediaries and travel operators. This study aims to examine the relationship linking students perspective of cognitive factors and their intentions to purchase online airline e-ticket from online travel agencies. Using convenience sampling, a total of 302 survey questionnaires were distributed to hospitality and tourism students in UiTM via google form. 245 responses were received and used for data analysis. Regression results revealed that two cognitive factors have significant relationships with students intentions to purchase airline e-ticket online. These include perceived risks and web security. Of these two attributes, web security have the most significant impact on students intentions to purchase airline e-ticket online. The study provides insights to online travel operators on the factors to concentrate in improving their services to customers as well as assist them in boosting their sales in the future and to achieve customer loyalty.